COVID‐19 knowledge prevents biologics discontinuation: Data from an Italian multicenter survey during RED‐ZONE declaration. Issue 4 (28th May 2020) - Bragazzi, Nicola Luigi; Riccò, Matteo; Pacifico, Alessia; Malagoli, Piergiorgio; Kridin, Khalaf; Pigatto, Paolo; Damiani, Giovanni
Abstract: SARS‐CoV‐2 become pandemics and there is still a dearth of data about its the potentially among dermatological patients under biologics. We aimed to assess health literacy, disease knowledge, treatment dissatisfaction and biologics attitudes toward COVID‐19. We performed a cross‐sectional, questionnaire‐based survey on 98/105 consecutive dermatological patients treated with biologics—51 suffering from plaque psoriasis, 22 from atopic dermatitis, and 25 from hidradenitis suppurativa. An ad hoc, validated questionnaire has 44 items investigating the following domains: knowledge of COVID‐19 related to (a) epidemiology, (b) pathogenesis, (c) clinical symptoms, (d) preventive measures, and (e) attitudes. Patients data and questionnaires were collected. Despite only 8.1% thought that biologics may increase the risk of COVID‐19, 18.4% and 21.4% of the patients were evaluating the possibility to discontinue or modify the dosage of the current biologic therapy, respectively. Globally, male patients ( P = .001) with higher scholarity level ( P = .005) displayed higher knowledge of COVID‐19. Patients with lower DLQI ( P = .006), longer disease duration ( P = .051) and lower scholarity ( P = .007) have thought to discontinue/modify autonomously their biologic therapy. At the multivariate logistic regression, only the knowledge of epidemiology and preventive measures resulted independent predictors of continuation vs discontinuation and modification vs no modification, respectively. Dermatologists should promote COVID‐19 knowledge to prevent biologics disruption.